Rare complication of lateral abdominal wall hematoma after coronary angioplasty - Natarajan, Ramesh (Journal of Cardiovascular Medicine and Cardiology, 2020)
Abdominal wall hematoma is a rare but potentially serious complication that may develop after percutaneous coronary interventional procedures. In particular, an oblique muscle hematoma caused by injury to the superficial circumflex iliac branch of the femoral artery is very rare. Most of these cases can be managed by conservative measures including hydration and blood component transfusion. However, when active bleeding continues, angiographic embolization or surgery might be needed. Here, we report an uncommon case of lateral abdominal wall hematoma following left femoral artery puncture during the performance of percutaneous coronary intervention by the retrograde approach in a totally occluded right coronary artery.